Role of attachment style and moral identity in ethical behaviour among secondary school adolescent students in Nsukka, Enugu State - Odo, Onyekachi M.; Onyishi, Ike E. (Journal of Psychology and Allied Disciplines, 2023)
This study examined the role of attachment style and moral identity in ethical behaviour among adolescent students. A total of 666 adolescents were selected from six (6) secondary schools in Nsukka. They comprised 365 male students (54.8%) and 301 female students (45.2%).Their ages ranged from 13 to 17 years with mean age of 15.4 (SD = 1.230). Results of the analysis revealed that mother trust/communication significantly and positively related to ethical behaviour (β = .27, p = .005). Mother alienation significantly and negatively related to relativism domain of ethical behaviour (β = -.12, p = .005). Father’s alienation significantly and negatively related to idealism domain of ethical behaviour (β = -.08, p = .005). Peer’s trust/communication significantly and positively related to relativism domain of ethical behaviour (β = .09, p = .005). Peer’s alienation significantly and negatively related to relativism domain of ethical behaviour (β = -.18, p = .005). The results also showed that moral self significantly and positively related to idealism domain of ethical behaviour (β = .08, p < .005). Moral integrity did not determine idealism and relativism domains of ethical behaviour. In attachment style, mother attachment is the highest contributors to the development of ethical behaviour followed by father and then peer; while moral self-play major role in moral identity in development of individual’s ethical behaviour.